Defence response of french bean to Uromyces appendiculatus induced by traizole and strobilurin fungicides - Singh, Gurvinder; Gupta, S K; Devi, Banita; Prasad, Pramod; Bhardwaj, S C (Indian Journal of Plant Protection, 2020)
The strobilurin and traizole group of fungicides comprise a variety of synthetic plant-protecting compounds with broad-spectrum antifungal activity. In the present study, azoxystrobin (1000 μg/ml), tebuconazle (1000 μg/ml), hexaconazole (1000 μg/ml) and mancozeb (2500 μg/ml) were evaluated for their efficacy in inducing Defence enzymes in French bean against Uromyces appendiculatus. The application of fungicides triggered the activity of Defence related enzymes viz., peroxidise (PO), polyphenol oxidase (PPO) and phenylalanine ammonia lyase (PAL) in bean plants upon challenge inoculation with U. appendiculatus. The activities of Defence enzymes reached a peak at five days after inoculation (DAI) with the pathogen and was found more in bean plants treated with azoxystrobin followed by tebuconazole and hexaconazole as compared to control while it was least in mancozeb.